THE FLEXIBLE UPPER FLOOR MADE OF LIGHT METAL STRUCTURES USING CROSS SYSTEMS - E. V. Nazarova; N. Y. Avetyan; A. S. Marutyan (Современная наука и инновации, 2023)
A method of increasing seismic resistance using flexible upper floors of newly erected buildings and structures, as well as reconstructed and repaired objects of existing buildings is presented. The technical solution of light metal structures of complete delivery from cross-farms included in the number of structural systems is given. In the general series of cross-systems, the modules of coatings and ceilings of the Pyatigorsk type are distinguished by their technical and economic indicators. Due to the compact dimensions of these modules, they can be made all-welded according to the original technology with a partial transfer of manufacturing from the workshop to the construction site, which provides them with a certain demand in the unstable conditions of the current market.